2010
DOI: 10.1007/s00198-010-1468-y
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture incidence in Lebanon: a national registry-based study with reference to standardized rates worldwide

Abstract: The hip fracture age-standardized incidence rates in the Lebanese subjects receiving Ministry of Health coverage were lower than those found in northern Europe and the US and closest to rates derived for southern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…It is well established that hip fracture rates vary markedly in different countries . International variations in hip fracture risk have been shown to have a latitudinal gradient which has prompted speculation that latitude might be a marker of sunlight exposure and, hence, of vitamin D status .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that hip fracture rates vary markedly in different countries . International variations in hip fracture risk have been shown to have a latitudinal gradient which has prompted speculation that latitude might be a marker of sunlight exposure and, hence, of vitamin D status .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that hip fracture rates vary markedly in different countries. (36,37) International variations in hip fracture risk have been shown to have a latitudinal gradient which has prompted speculation that latitude might be a marker of sunlight exposure and, hence, of vitamin D status. (38) In an analysis of a study reporting hip fracture rates around the world, (9) it was reported that there was approximately a 4% increment in hip fracture incidence for each 1°latitude difference from the equator.…”
Section: Latitudementioning
confidence: 99%
“…The only data on hip fracture trends in the Middle East comes from representative data on hip fracture rates from the Lebanese National Hip Fracture registry, for years 2007 to 2012 in men and women above 50 years of age (71) (Ahmadieh H, El-Hajj Fuleihan G, unpublished data). It showed no change in age-standardized rates in either gender.…”
Section: Middle Eastmentioning
confidence: 99%
“…A variety of studies have examined hip fracture rates in different regions of the world [511]. Greater than 10-fold differences have been found, largely on the basis of register studies undertaken on a regional or national level and at different calendar years.…”
Section: Introductionmentioning
confidence: 99%